If lo g 1 8 3 6 = x and lo g 2 4 7 2 = y . Find the value of 4 ( x + y ) − 5 x y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You have shown that x = 1 + 1 + 2 v 1 and y = 1 + v + 3 v .
Since the answer is 2, in hindsight, you can prove that ( 5 x − 4 ) ( 5 y − 4 ) = 6 .
Then expand and rearrange the terms to get the expression in question.
That is a really good way, I didn't realize it! 👍
4 ( x + y ) − 5 x y = 4 ( lo g 1 8 3 6 + lo g 2 4 7 2 ) − 5 lo g 1 8 3 6 lo g 2 4 7 2 = 4 ( lo g 6 1 8 lo g 6 3 6 + lo g 6 2 4 lo g 6 7 2 ) − 5 ⋅ lo g 6 1 8 lo g 6 3 6 ⋅ lo g 6 2 4 lo g 6 7 2 = 4 ( lo g 6 3 + 1 2 + 2 lo g 6 2 + 1 lo g 6 2 + 2 ) − 5 ⋅ lo g 6 3 + 1 2 ⋅ 2 lo g 6 2 + 1 lo g 6 2 + 2 = ( 2 lo g 6 2 + 1 ) ( lo g 6 3 + 1 ) 4 lo g 6 2 lo g 6 3 + 1 0 lo g 6 2 + 8 lo g 6 3 − 4 = 2 lo g 6 2 lo g 6 3 + 2 lo g 6 2 + lo g 6 3 + 1 4 lo g 6 2 lo g 6 3 + 2 lo g 6 2 + 8 ( lo g 6 2 + lo g 6 3 ) − 4 = 2 lo g 6 2 lo g 6 3 + lo g 6 2 + 2 4 lo g 6 2 lo g 6 3 + 2 lo g 6 2 + 4 = 2
Problem Loading...
Note Loading...
Set Loading...
Pretty sure there are much simpler ways to do this, but here's my first (successful) approach:
For the working below, treat x as u (I don't know why I used x )